Role of Clusterin in the Female Reproductive System - Shrestha, Eliza; Yang, Yue-bo; Li, Xiao-Mao (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i2.5069 NJOG 2010 Nov-Dec; 5(2): 3-7